REVITALISASI INFORMASI SEJARAH DAN PETA DESA MELALUI PEMBAHARUAN PAPAN INFORMASI DAN PETA DESA NGEGEDHAWE SEBAGAI SARANA EDUKASI DAN TRANSPARANSI PUBLIK - Polikarpus Stefanus Bani Dena; Rodriques Servatius (Journal Education and Government Wiyata, 2026)
Community service for revitalizing historical information and village maps was carried out because the existing village information boards did not present the history and village maps well, both in terms of content and physical condition. With this community service program, historical information and village maps were updated through the rejuvenation of information boards so that they were attractive, functional, and easily accessible to residents. This information board can increase community knowledge regarding the village area and the history of the village's formation, as well as its existing potential. The creation of this information board used a location survey method, data collection through interviews with community leaders, designing a village map, making and installing the board at a predetermined location. On this information board, a village map, a brief historical narrative of the village's formation, and the potential that exists in the village, such as in the fields of agriculture and animal husbandry, were listed. The community was very enthusiastic about the creation of this information board, because it can be an educational medium, and can strengthen the local identity of the Ngegedhawe village community.